Secondary school Saudi students' attitudes towards using educational blogs in learning english and the influence of blogs on students' achievement - Sultan, Noura (Institute of Education,International Islamic University Malaysia, 2012)
The present study attempts to investigate the attitudes of Saudi secondary school students' towards the use of educational blog in learning English and the influence of using blog on their achievement. The attitudes of students who experienced blog in learning English were probed using 38-item questionnaire. A pre-test/post test experimental and control group design was used for data collection. Both methods were exposed to pre-post means of getting data. The sample of this study consisted of 30 students who are studying at the Saudi Arabia secondary school. The findings showed that the students who read, commented and were involved with the blog had positive attitudes towards using educational blog in learning English. The study also found that there is a statistically significant difference between the means scores of the treatment group and the control group in the achievement test based on the method of teaching (using blog-traditional method) in favour of the experimental group. There is a statistically significant difference between the treatment group students' pre and post means scores in attitudes questionnaire when comparing them in favour of the post administration.